Pragmatic Bioethics - Holland, S. (2004)
Edited by G McGee. Bradford Book, 2003, $26.95, pp 320. ISBN 0262632721 The point of Pragmatic Bioethics is to view bioethics through the lens of American pragmatism. The book is in three parts. The papers in part one look at the “pragmatic method” and bioethics in general; those in part two are intended to suggest that bioethical debates can be informed by parts of the canon of classical American pragmatism; those in part three apply aspects of pragmatism to specific bioethical issues more overtly. This structure is odd in two related respects: the difference between the papers in parts two and three is unclear, and papers dealing in similar ways with similar bioethical issues (for example, death and dying) are placed in each of these parts. My view of how philosophy does, and should, apply to bioethics is at odds with that implied by Pragmatic Bioethics. I think bioethics can be informed by philosophy in two ways. Firstly, specific bioethical problems can be elucidated by substantive philosophical data (including normative theoretical advances, and specific philosophical theories such as those pertaining to personal identity). Secondly, and more pervasively, bioethics would benefit from acquiring certain intellectual habits distinctive of (analytic) philosophy (notably, conceptual clarity, argumentative rigour, and accuracy of expression). The different view taken in this book is that bioethics might look to the methodology implied by American pragmatism, and specific bioethical issues might be addressed by reference to American pragmatist writings. I feel that this different view was only partially convincing. There are two main sets …
Keywords: Rezension